Реконструкція зображень з використанням глибинного навчання - Біляєва, Є. І. (ХНУРЕ, 2023)
This work describes a study of the possibilities of applying neural network technologies to restore the quality of photographs. The work considers various recovery methods based on neural network algorithms and describes achievements in this field. The results showed that neural network algorithms allow the achievement of high accuracy in restoring the quality of photographs and have the potential to be applied in various fields such as medicine, science, art, etc.
Keywords: глибинне навчання; реконструкція зображень